Legal Aspects of Liability in the Sharia Banking Financing System: Its Position and Application - Suran Ningsih, Ayup; Puspa Wardhani, Harumsari (Law Research Review Quarterly, 2024)
The writing of this article aims to explain the definition of liabilities and Sharia banking, knowing how the legal position of liabilities is as a form of guarantee in Sharia banking financing, implementation/implementation of liabilities in Sharia banking financing, and to find out whether the liability as a form of guarantee in Islamic banking financing has a position equivalent to credit in conventional banking. Many references are used to explain the formulations of the problem. Methodological techniques were used in this study, including describing and explaining the rights of Islamic banks and dependents, and the position between Islamic banking financing and credit in conventional banking. This article uses a normative legal approach method with secondary data sources, i.e., the original legal text, secondary legal literature, and non-legal sources so that it can be concluded, that: 1. The validity of the Rights of Liability in financing Islamic banking can be observed through the existence of the Rights of Liability institution regulated in Law No. 4 of 1996 concerning the Rights of Liability to Land and Related Objects. 2. In the practice of sharia banking, there is a strong emphasis on the existence of collateral in assessing and providing financing to customers. 3. Hak Tanggungan as a form of guarantee has different positions between conventional and sharia banks.